Lacunae in Curriculum Design and Delivery - Pilla, M. Deva Santhanam (International Journal For Research In Educational Studies, 2015)
The ESL/EFL learners are from very diverse backgrounds and of course possess varying abilities and discordantly diverse requirements. The learning styles and aptitudes of one student are very different from another’s. But most private universities and colleges are not designing their curriculum keeping in mind the job/market/industry needs or the diversity in the classroom. The employability of these students is seriously affected by these lacunae in the system. To add insult to injury, teachers in these universities and colleges are not helping the cause in most cases. Unless these universities and colleges devote their energies to preparing rounded, world-ready, market-ready individuals, they will be failing in their duty and will be squarely blamed for this disservice. Hence, some soul searching has to be done to remedy this malady before the malaise proves to be beyond cure. This paper attempts to throw light on some of these issues and suggests a few remedies.